(3JegjO GdbhGYO TQM JSgjd GdahGFOs - (3eMH GdOjf eMeO Hf jhSa Hf CMeO GdMdHj GdeUQj GdeYQha H`` fGXQ GdLjTs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3U(B: (3HGH GdEVGaI(B: (3GdeVGa gh GdGSe GdeLYhd cLRA NGaVkG dg HeYfi aj Ef MSf JbOjQgG hMOgG s
(3BNQgG (B:s
(3hCf GdLhGH eMPha aj GdGKfJjf hcPG aj GdHjJ GdPj PcQg Je GdLRA GdKGdK jJdhg GdLRA GdQGHY s
(3fSNI KGdKIs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
Keywords: (3GdfMhs